As crianças da República: imagens sobre culturas infantis no centro da cidade de São Paulo - Casciano, Bruna Serena (Universidade Federal de São Carlos, 2025)
This study aimed to understand how children living in the República neighborhood, in the central area of ​​the city of São Paulo, create and act in their daily lives. Throughout this study, we sought to answer some central questions, together with the children, through an ethnographic procedure, such as: What does this group of children do when and while they walk around the city? Where do they go? With what, with what, how and with whom do they play? How do they relate and interact with the city space? What characterizes the cultures they produce? How do they understand and construct their lived spaces in the city through their daily experiences? The main objective was to understand how children relate to the sociocultural context in which they are inserted, making it possible to identify which children's culture is produced by them and how they appropriate the urban space in which they live. The research is based on the theoretical framework of the sociology of childhood, and the research with children was conducted based on written reports, obtained from their speech, photographs and drawings, also produced by the children. The research carried out with the children in the city center of São Paulo allowed us to observe the urban gaps they found to play and produce their peer culture. The experiences of the children of the Republic, who, accompanied by their caregivers, enjoy a certain autonomy to experiment and play, occur daily in Roosevelt Square, whose adult-centric logic of use is subverted and restructured by them: objects and equipment in the square gain new uses and are requalified. The urban daily life of these children, despite taking the same routes from their homes to school or to the square every day, is never the same; there are always new perceptions that the space, the streets and the sidewalks provide. The space of Praça Roosevelt, a favorite place for children but not so well-liked by nannies, is described by the former as representing affection, belonging and friendship. It was possible to verify that my interlocutors, mostly white and from the urban middle class, share among themselves, in their speeches and games, elements of a broader media culture aimed at children, namely: Pokémon cartoons, Paw Patrol, etc. Despite the fissure that the children of the Republic generate in a space aimed and designed for adult use, Praça Roosevelt is perceived as a relatively homogeneous space, with regard to the presence of children's groups, bringing evidence of a certain racialization of the space.
Children of the Republic: images of children's cultures in downtown São Paulo
Keywords: Culturas infantis; Imagens; Cidade; Educação; Fotografia; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO